2006
DOI: 10.1074/jbc.m600577200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polyphenol Oxidase Mined from a Metagenome Expression Library of Bovine Rumen

Abstract: RL5, a gene coding for a novel polyphenol oxidase, was identified through activity screening of a metagenome expression library from bovine rumen microflora. Characterization of the recombinant protein produced in Escherichia coli revealed a multipotent capacity to oxidize a wide range of substrates (syringaldazine > 2,6-dimethoxyphenol > veratryl alcohol > guaiacol > tetramethylbenzidine > 4-methoxybenzyl alcohol > 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) Ͼ Ͼ phenol red) over an unusually b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(44 citation statements)
references
References 42 publications
(29 reference statements)
1
43
0
Order By: Relevance
“…(42,43), while the lcc4 genes are often overlooked in soils. Furthermore, the lcc4 genes are different from and lack homology to the lcc3 genes (44). In our metagenomes, the relative abundance of sequences assigned to both the lcc3 oxidase and dioxygenases decreased 6-fold from the surface to the deeper portions of the bog (Table 2).…”
Section: Resultsmentioning
confidence: 95%
“…(42,43), while the lcc4 genes are often overlooked in soils. Furthermore, the lcc4 genes are different from and lack homology to the lcc3 genes (44). In our metagenomes, the relative abundance of sequences assigned to both the lcc3 oxidase and dioxygenases decreased 6-fold from the surface to the deeper portions of the bog (Table 2).…”
Section: Resultsmentioning
confidence: 95%
“…Due to the inhibition of Lcp1 VH2 activity by the utilized chelating agents with a simultaneous absence of metals other than copper and the results of the applied bathocuproine sulfonate-based spectroscopic assays, and since it is known from the literature that hexahistidine-tagged, purified, copper-binding enzymes do not contain significantly larger amounts of copper than the same proteins that were purified by applying streptavidin tags or for which the hexahistidine tag was removed (43,44), it can be concluded that purified Lcp1 VH2 possesses Cu(II) as a transition factor. The divalent copper ions are known to preferably complex with histidine, serine, threonine, or tyrosine amino acid residues (45).…”
Section: Discussionmentioning
confidence: 99%
“…Laccases are produced by bacteria (Beloqui et al, 2006), insects (Dittmer et al, 2004), plants (O'Malley et al, 1993) and fungi (Basidomycota and Ascomycota). Laccases produced by white-rot fungi (Basidiomycota) currently receive particular attention due to their apparent ability to catalyze the modification and depolymerization of lignin and in this way assist in the decomposition of plant material.…”
Section: Introductionmentioning
confidence: 99%